Dutasteride nanoemulsion preparation to inhibit 5‐alpha‐hair follicle reductase enzymes in the hair follicle; an ex vivo study. Issue 1 (31st October 2022) - Memar Bashi Aval, Mehri; Hoveizi, Elham; Mombeiny, Reza; Kazemi, Mostafa; Saeedi, Saeedeh; Tavakol, Shima
Abstract: Alopecia is a treatable disorder that usually occurs due to high levels of 5‐alpha dihydrotestosterone in hair follicles. To enhance the storage capacity of hair follicles and alleviate the inherent characteristics of dutasteride, 5‐alpha reductase inhibitor, a prolonged‐release nanocarrier was synthesised, and its influence on rat abdomen's skin was investigated. Results showed the lower ratio of S/Co (higher ethanol concentration) increased the hydrodynamic nanocarriers' particle size due to thermodynamic disturbance and Ostwald ripening. In contrast, an increase in surfactant through a decrease in interfacial tension resulted in smaller nanocarriers of 32.4 nm. Moreover, an increase in viscosity had an inverse correlation with the nanoemulsions' particle size. Nanocarriers containing ethanol showed less entrapment efficacy, perhaps due to the rapid dissolution of dutasteride into ethanol during nanoemulsification, while, based on Stokes' equation, the addition of ethanol resulted in smaller particle size and stability of the system. Skin permeation analysis using Franz diffusion cells showed nanocarriers could pass through the skin and release dutasteride for 6 days. In conclusion, the optimum concentration of ingredients is decisive in guaranteeing the ideal particle size, stability, and skin permeation of nanocarriers. The Present dutasteride nanocarrier would promise a prolonged and sustained‐release drug delivery system for Alopecia therapy. Abstract : Alopecia is a treatable disorder that, over time, gets to be chronically influencing a noteworthy part of the population. To enhance the storage capacity of hair follicles and alleviate the inherent characteristics of dutasteride, a prolonged‐release nanocarrier was synthesised that could pass through the skin and release dutasteride for more than six days. The synthesised dutasteride nanocarrier would promise a prolonged and sustained‐release drug delivery system for Alopecia therapy.